A comparing the treatment of pain with continuous epidural analgesia versus systemic analgesia in patients with hip fracture - Temelkovska Stevanovska, Marina; Kuzmanovska, Biljana; Kartalov, Andrijan; Panovska Petrusheva, Aleksandra (SHMSHM - AAMD, 2015)
Introduction: The systemic postoperative analgesia is unefficient in most of the patients with hip fracture, which is the reason for pain, especially during leg movement. Continuous epidural analgesia is efficient option for pre and post operative pain relief. The aim of this study was to compare the effect of continuous epidural analgesia versus sistemic analgesia, as a pre- and post operative analgesia in patients with hip fracture. Methods: Sixty patients with hip fracture were included and were randomly assigned to two groups of 30 patients: SA group –patients with sistemic analgesia; and EDC group - patients with a continuous epidural analgesia. In all patients pain intensity was measured at rest and passive hip flexion by using VDS (0 – 4) in several intervals: 1 and 12h before surgery, after analgesic treatment and 24 and 48 hours after intervention. The motor blockade was measured at the same times only in patients from EDC group, along with the side effects in both groups. Results: The values of VDS were significantly lower in patients from EDC group versus patients from SA group in rest and movement in all time intervals for p<0.05. Motor block was 0 in all patients from EDC group according to modified Bromage score. Registered side effects were sedation, dizziness itching and urine incontinence. Conclusion: Pain relief in pre- and post operative period has been superior in EDC group versus SA group at rest and movement in patients with hip fracture.
Keywords: postoperative analgesia; epidural anesthesia; elderly; hip fracture